Pendidikan Agama Anak Nelayan di Desa Meucat, Kecamatan Samudera, Kabupaten Aceh Utara - Muammar Muammar (DAYAH: Journal of Islamic Education, 2019)
This study entitled "The Religious Education of the Fishermen’s Children of Meucat Village of Samudera Sub-district of Aceh Utara District" formulated several research questions, they are: 1) How is the quality of the religious education of the children of the fishermen in Meucat Village? 2) What are the strategies employed by the parents in providing the religious education in Meucat Village? and 3) What are the challenges faced by the parents in their effort to fulfill their children's religious education in Meucat Village? The study used a qualitative approach with an analytical descriptive method, aiming to describe and analyze the social phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals and groups. The subjects of this study were the children of fishermen, the fishermen, the teachers of Islamic Religious Education, the village head, and the community figures of Meucat Village, Samudera Sub-district, North Aceh District.